Military Otolaryngology Resident Case Numbers and Board Passing Rates during the Afghanistan and Iraq Wars. (18th February 2014) - Scalzitti, Nicholas; Brennan, Joseph; Bothwell, Nici; Brigger, Matthew; Ramsey, Mitchell; Gallagher, Thomas; Maturo, Stephen
Abstract : Objective: During the wars in Iraq and Afghanistan, the US military has continued to train medical residents despite concern that postgraduate medical education at military training facilities has suffered. This study compares the experience of otolaryngology residents at military programs with the experience of their civilian counterparts. Study Design: Retrospective review. Setting: Academic military medical centers. Subjects and Methods: Resident caseload data and board examination passing rates were requested from each of the 6 Department of Defense otolaryngology residency programs for 2001 to 2010. The American Board of Otolaryngology and the Accreditation Council for Graduate Medical Education provided the national averages for resident caseload. National board passing rates from 2004 to 2010 were also obtained. Two‐sample t tests were used to compare the pooled caseloads from the military programs with the national averages. Board passing rates were compared with a test of proportions. Results: Data were available for all but one military program. Regarding total cases, only 2001 and 2003 showed a significant difference ( P < . 05), with military residents completing more cases in those years. For individual case categories, the military averages were higher in Otology (299.6 vs 261.2, P = . 033) and Plastics/Reconstruction (248.1 vs 149.2, P = . 003). Only the Head & Neck category significantly favored the national average over the military (278.3 and 226.0, P = . 039). The first‐time board passing rates were identical between the groups (93%). Conclusion: Our results suggest that the military otolaryngology residency programs are equal in terms of caseload and board passing rates compared with civilian programs over this time period.